2016
DOI: 10.1155/2016/9408190
|View full text |Cite
|
Sign up to set email alerts
|

Prognostic Importance of Cell Cycle Regulators Cyclin D1 (CCND1) and Cyclin-Dependent Kinase Inhibitor 1B (CDKN1B/p27) in Sporadic Gastric Cancers

Abstract: Background. Gastric cancer is known for a notable variety in the course of the disease. Clinical factors, such as tumor stage, grade, and localization, are key in patient survival. It is expected that molecular factors such as somatic mutations and gene amplifications are also underlying tumor biological behavior and may serve as factors for prognosis estimation. Aim. The purpose of this study was to examine gene amplifications from a panel of genes to uncover potential prognostic marker candidates. Methods. A… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 52 publications
0
6
0
Order By: Relevance
“…To determine if ALX1 function is required for cell cycle progression, we investigated expression of Cyclin D1 (CCND1), required for the cell cycle G1/S transition, and Cyclin A2 (CCNA2), required for the DNA synthesis during the S-phase, were investigated. Both cyclins are expressed throughout the active cell cycle, from the G1/S transition to the G2/M transition (Minarikova, Benesova et al, 2016, Pagano, Pepperkok et al, 1992. Expression levels of CCND1 and CCNA2 were compared between control and ALX1 165F/165F NCC at passages 2 and 3 post-differentiation.…”
Section: Increased Sensitivity To Apoptosis In Alx1 165f/165f Nccmentioning
confidence: 99%
“…To determine if ALX1 function is required for cell cycle progression, we investigated expression of Cyclin D1 (CCND1), required for the cell cycle G1/S transition, and Cyclin A2 (CCNA2), required for the DNA synthesis during the S-phase, were investigated. Both cyclins are expressed throughout the active cell cycle, from the G1/S transition to the G2/M transition (Minarikova, Benesova et al, 2016, Pagano, Pepperkok et al, 1992. Expression levels of CCND1 and CCNA2 were compared between control and ALX1 165F/165F NCC at passages 2 and 3 post-differentiation.…”
Section: Increased Sensitivity To Apoptosis In Alx1 165f/165f Nccmentioning
confidence: 99%
“…To determine whether ALX1 function is required for cell cycle progression, we investigated expression of Cyclin D1 (CCND1), required for the cell cycle G1/S transition, and Cyclin A2 (CCNA2), required for the DNA synthesis during the S-phase. Both cyclins are expressed throughout the active cell cycle, from the G1/S transition to the G2/M transition (Pagano et al, 1992;Minarikova et al, 2016). Expression levels of CCND1 and CCNA2 were compared between control and ALX1 165F/165F NCC at passages 2 and 3 post-differentiation.…”
Section: Generation and Characterization Of Ipsc-derived Nccmentioning
confidence: 99%
“…For CRC, it has been reported that the absence or reduction of CDKN1B expression is associated with a poor prognosis 35 . In contrast, CDKN1B gene amplification is associated with poor prognosis for gastric carcinomas 36 . High CDKN1B expression predicts sensitivity to hormone therapies and chemotherapy in luminal breast cancer patients, while its downregulation predicts resistance to radiotherapy and anti‐ERBB2 therapies 37 .…”
Section: Discussionmentioning
confidence: 99%